Factors Which Influence Effectiveness Prevention Transmission HIV From Mother to Child - Solikhah, Fitriana Kurniasari; Astuti, Erlina Suci (Tarqabin Nusantara Group, 2023)
ABSTRACT East Java has a high prevalence of HIV/AIDS, where there are 6957 women aged 15-49 years suffering from HIV/AIDS. This problem can cause transmission of HIV/AIDS to the baby even baby deaths due to HIV. This research aims to analyze the influencing factors sustainability program PPIA. Study use method qualitative with collectorlan data through interview deep. Study done in East Java, Service Health City East Java from January 2015 until June 2015. Population study is all power health in East Java city health service, and the sample was 12 people including the head of the UPT AIDS TB, head sexy P2PL, head community health center, head KIA, staff KIA And underwriter answer HIV Public health center. Sampling was purposive sampling and data was analyzed by triangulation. PPIA does not succeed Because low his K1 And Also K4, Where There is Public health center Which own K4 only 58%. At the Abepura hospital, 8 babies born with HIV were found, this was because the pregnant women were positive who do not take ARVs regularly until giving birth. The low K1 is also caused by several factors, namely pregnant women are more interested in going to medical practitioners, husbands who do not agree if wife his get test VCT, And low his awareness Mother pregnant will importance K1 until K4 And Also VCT. So Also with SIHA Which No walk with Good